Metformin and asarone inhibit HepG2 cell proliferation in a high glucose environment by regulating AMPK and Akt signaling pathway - Bhrigu Kumar Das; Rachel M. Knott; Pramod C. Gadad (SpringerOpen, 2021)
Abstract Background Metabolic dysregulation is one of the hallmarks of tumor cell proliferation. Evidence indicates the potential role of the 5'adenosine monophosphate-activated protein kinase (AMPK) and protein kinase B/Akt signaling pathway in regulating cell proliferation, survival, and apoptosis. The present study explores the effect of metformin HCl and the combination of α- and β-asarone on the proliferation of HepG2 cells in the presence of high glucose levels simulating the diabetic-hepatocellular carcinoma (HCC) condition. Results The metformin and asarone reduced HepG2 cell viability in a dose-dependent manner and induced morphological changes as indicated by methyl thiazolyl tetrazolium (MTT) assay. The metformin and asarone arrested the cells at the G0/G1 phase, upregulated the expression of AMPK, and downregulated Akt expression in high glucose conditions as identified by the flow cytometry technique. Further, the upregulated AMPK led to a decrease in the expression of phosphoenolpyruvate carboxykinase-2 (PCK-2) and sterol regulatory element-binding protein-1 (SREBP-1). Conclusion The anti-proliferative effect of metformin and asarone in the diabetic-HCC condition is mediated via AMPK and Akt pathway.